THREE-DIMENSIONAL REAL ESTATE CADASTRE. PROBLEMS OF STORAGE AND INFORMATION MANAGEMENT: Array - Pomortseva, O. (Municipal economy of cities (Technical science), 2019)
The article discusses the requirements for a geographic information system, on the basis of which a three-dimensional real estate cadastre can be formed. The use of geographic information systems will allow to combine operations for working with databases, visualization and spatial analysis. It is proposed to use the existing two-dimensional cadastral portal with a three-dimensional browser to present a realistic image of real estate objects. Today, infrastructure is becoming more complex. Territory development becomes complex and requires registration of legal status. With the existing two-dimensional registration, this can be realized only partially. The transition from a two-dimensional to a three-dimensional registration system is a matter of time. Working with cadastral information involves working with large amounts of data. To work, a database management system is required. It is necessary to store data, create different user requests. You also need to create realistic visualizations for displaying property objects. In parallel, there are questions related to the preservation of information. There are questions about the protection of information and its use. It is necessary to develop a three-dimensional geo-information system with verification of objects in relation to formal rules. This system should support database management and information security. The article also describes the structure of the main components of a three-dimensional geographic information system. The most important factors that are needed for such a geographic information system are flexibility, scalability and compatibility. The three-dimensional geo-information system that will be used to develop a three-dimensional inventory should create three-dimensional models of buildings and infrastructure or work with imported models. Such a system should provide the ability to store large amounts of information. It must manage this information and allow the use of this information to different groups of consumers. Such a system should perform spatial analysis and various types of research. This is necessary for the design of infrastructure facilities.